PENGARUH PEMBERIAN NITROGEN DAN JUMLAH ANAKAN TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SORGUM (Sorghum bicolor (L.) Moench) LOKAL PASURUAN - sulistyawati; Pratiwi, Sri Hariningsih; Firdaus, Rizqy Zukhrufatul (Universitas Veteran Bangun Nusantara, 2023)
Sorghum is cereal crop that can form tillers as new individuals, suitable for cultivation in Indonesia and can be a staple food substitute for rice. One of the efforts in increasing production is through the regulation of the number of tillers and nitrogen nutrients which play a major role in the process of vegetative growth and regulation. This study aimed to determine the interaction between nitrogen dose and number of tillers, the effect of nitrogen dose and the effect of the number of tillers on the growth and yield of Pasuruan local sorghum plants. The research was conducted in Pohjentrek Village, Purworejo District, Pasuruan City in December 2022 - April 2023. The soil used had a pH of 7.0 with N content of 0.11%, P2O5 11.06 ppm and K2O 0.13 ppm. The study was arranged in a Factorial Randomized Block Design (two factors), the first factor was nitrogen dosage (U) with levels U1 = 50% nitrogen, U2 = 75% nitrogen, U3 = 100% nitrogen and the second factor was the number of tillers (P) with levels P1 = 1 tiller, P2 = 2 tillers and P3 = 3 tillers. Each treatment combination was repeated three times so there were 27 treatment units. The data obtained from the study were analyzed using analysis of variance (F test), if there was a significant effect then continued with the BNT test at the 5% level. The results showed that the highest production was found in the combination of 100% nitrogen with 1 tiller, which amounted to 5.44 tons ha-1, followed by a combination of 75% nitrogen with 1 tiller at 4.49 tons ha-1 and the lowest results in the combination of 100% nitrogen with 2 tillers at 4.49 tons ha-1.